2019
DOI: 10.5194/essd-11-1037-2019
|View full text |Cite
|
Sign up to set email alerts
|

A compilation of global bio-optical in situ data for ocean-colour satellite applications – version two

Abstract: A global compilation of in situ data is useful to evaluate the quality of ocean-colour satellite data records. Here we describe the data compiled for the validation of the ocean-colour products from the ESA Ocean Colour Climate Change Initiative (OC-CCI). The data were acquired from several sources (including, inter alia, MOBY, BOUSSOLE, AERONET-OC, SeaBASS, NOMAD, MERMAID, AMT, ICES, HOT and GeP&CO) and span the period from 1997 to 2018. Observations of the following variables were compiled: spectral remotese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…The instruments are typically installed on offshore platforms like lighthouses, oceanographic and oil towers. AERONET-OC is instrumental in satellite ocean colour validation activities through standardized measurements performed at different sites with a single measuring system and protocol, calibrated with an identical reference source and method, and processed with the same code [48][49][50]. In recent years, AERONET-OC has also supported the radiometric characterization of Landsat-8 and Sentinel-2 for aquatic applications [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and, even if for a limited set of bands, we have considered this network very relevant also for PRISMA.…”
Section: Aeronet-oc System and Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The instruments are typically installed on offshore platforms like lighthouses, oceanographic and oil towers. AERONET-OC is instrumental in satellite ocean colour validation activities through standardized measurements performed at different sites with a single measuring system and protocol, calibrated with an identical reference source and method, and processed with the same code [48][49][50]. In recent years, AERONET-OC has also supported the radiometric characterization of Landsat-8 and Sentinel-2 for aquatic applications [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and, even if for a limited set of bands, we have considered this network very relevant also for PRISMA.…”
Section: Aeronet-oc System and Networkmentioning
confidence: 99%
“…The WISPStation is an autonomous radiometer system developed by Water Insight B.V. (Wageningen, The Netherlands). The system is calibrated relative to a reference instrument (calibrated in a certified laboratory using a lamp and an integrating sphere with NIST traceable calibrations) and its usefulness in gathering quality-controlled water reflectance data has been demonstrated over a variety of inland waters [47][48][49][50][51][52][53]. The WISPStation contains two sets of sensors, measuring both the radiance and irradiance near instantaneous at high frequency in the spectral range of 350-900 nm every 15 min.…”
Section: Wispstation Systemmentioning
confidence: 99%
“…The in situ database is composed of three distinct datasets containing multi-spectral R rs and b bp : the recently updated global in situ database ( [33] hereafter V19 dataset), an in situ dataset collected by the Italian National Research Council (CNR) during two field campaigns in the Mediterranean Sea ( [29] hereafter CNR dataset) and the time-series of data acquired by the BOUSSOLE buoy in the northwestern Mediterranean Sea ( [34,41]; hereafter BOU dataset [42]). The three in situ databases were quality-checked as described below.…”
Section: Assessment Of the Quasi-analytical Algorithm (Qaa)mentioning
confidence: 99%
“…In order to provide a best-effort b bp uncertainty assessment, this work aims at evaluating the efficiency of QAA for global b bp retrievals by using a large database of corresponding in situ R rs and b bp data (N = 2881). In details, we use the updated version of the recent in situ global bio-optical dataset [33] together with field measurements from the BOUSSOLE buoy [34] and two different oceanographic cruises in the Tyrrhenian and Adriatic Seas. Unlike previous studies [29], here, the QAA performance is considered at multiple bands that further allow the evaluation of the b bp spectral slope retrievals against in situ measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Torrecilla et al (2011) demonstrated that hyperspectral data of phytoplankton absorption and remote-sensing reflectance provide improved discrimination of dominant phytoplankton groups in open-ocean environments compared with multispectral data. High spectral resolution aquatic remote sensing significantly improves retrievals of optical constituents in inland, coastal, and polar aquatic environments, where these environments exhibit significant smaller-scale temporal and spatial variability, increased decoupling between in-water constituents, and a greater dynamic range in parameter values compared to the open ocean (Mouw et al, 2015;Bell et al, 2015;Dierssen et al, 2015;Hu et al, 2015;Vandermeulen et al, 2017). In inland, coastal, and polar aquatic areas, dissolved organic matter (DOM) and non-algal particles (NAP) play a more important role in affecting the color of water, as well as its biogeochemistry, sediment transport, and primary productivity (Devred et al, 2013;Mouw et al, 2017).…”
Section: Introductionmentioning
confidence: 99%